Bridging the Participatory Gap: Children with Disabilities and Disaster Risk Reduction. Issue 3 (November 2017) - Ronoh, Steve; Gaillard, J.C.; Marlowe, Jay
Disaster risk reduction (DRR) needs to be inclusive. However, potentially vulnerable groups such as children with disabilities are often excluded. Their perceptions and views are overlooked due to existing structural forms of exclusion and lack of inclusive methods that enable children to effectively contribute to DRR. This paper provides an insight into understanding the complexities of DRR participation among twenty-seven children with disabilities from three case study schools in New Zealand. It explores the notion of 'participation' through flexible participatory tools. It involved mapping of safe and unsafe areas of their class and the school during a disaster, and proportional piling activities representing identified potential natural hazards in their region. The approach was able to accommodate and permit a sustained continuum of engagement among children with diverse disabilities, capacities and experiences. Crucially, it offers a bridge that recognizes communication as a two-way process between adults and children, where adults learn how children express their views, thus according them a voice in DRR.